Group Counseling with Self-Talk Technique and Stress Inoculation Training to Enhance Students’ Eustress (Universitas Negeri Semarang, 2019)
This study aims to test the effectiveness of group counseling with self-talk technique and stress inoculation training technique to enhance students’ eustress. This study employed 2x2 factorial design by involving 28 students of Public Senior High School 12 Semarang. The technique of data analysis used was 2-path ANAVA test and the difference of means. The result of the study showed that group counseling with self-talk technique and stress inoculation training technique is effective in enhancing students’ eustress. This finding confirms the effectiveness of group counseling service with self-talk technique and stress inoculation training technique for students in Semarang, Indonesia.